Escape from thymic deletion and anti-leukemic effects of T cells specific for hematopoietic cell-restricted antigen - Ji-Min Ju (Nature Portfolio, 2018)
Antigen distribution patterns affect thymic negative selection. Here, the authors show that incomplete thymic negative selection occurs to T cells for hematopoietic cell-restricted antigen H60 in mice, driving graft-versus-leukemia after H60-mismatched bone marrow transplantation.